Fixed Point Theorems in Quaternion-Valued Metric Spaces - Ahmed El-Sayed Ahmed; Saleh Omran; Abdalla J. Asad (Abstract and Applied Analysis)
The aim of this paper is twofold. First, we introduce the concept of quaternion metric spaces which generalizes both real and complex metric spaces. Further, we establish some fixed point theorems in quaternion setting. Secondly, we prove a fixed point theorem in normal cone metric spaces for four self-maps satisfying a general contraction condition.